6S-2 RNA deletion in the undomesticated B. subtilis strain NCIB 3610 causes a biofilm derepression phenotype. Issue 1 (2nd January 2021) - Thüring, Marietta; Ganapathy, Sweetha; Schlüter, M. Amri C.; Lechner, Marcus; Hartmann, Roland K.
ABSTRACT: Bacterial 6S RNA regulates transcription via binding to the active site of RNA polymerase holoenzymes. 6S RNA has been identified in the majority of bacteria, in most cases encoded by a single gene. Firmicutes including Bacillus subtilis encode two 6S RNA paralogs, 6S-1 and 6S-2 RNA. Hypothesizing that the regulatory role of 6S RNAs may be particularly important under natural, constantly changing environmental conditions, we constructed 6S RNA deletion mutants of the undomesticated B. subtilis wild-type strain NCIB 3610. We observed a strong phenotype for the ∆6S-2 RNA strain that showed increased biofilm formation on solid media and the ability to form surface-attached biofilms in liquid culture. This phenotype remained undetected in derived laboratory strains (168, PY79) that are defective in biofilm formation. Quantitative RT-PCR data revealed transcriptional upregulation of biofilm marker genes such as tasA, epsA and bslA in the ∆6S-2 RNA strain, particularly during transition from exponential to stationary growth phase. Salt stress, which blocks sporulation at a very early stage, was found to override the derepressed biofilm phenotype of the ∆6S-2 RNA strain. Furthermore, the ∆6S-2 RNA strain showed retarded swarming activity and earlier spore formation. Finally, the ∆6S-1&2 RNA double deletion strain showed a prolonged lag phase of growth under oxidative, high salt and alkaline stress conditions, suggesting that the interplay of both 6S RNAs in B. subtilis optimizes and fine-tunes transcriptomic adaptations, thereby contributing to the fitness of B. subtilis under the unsteady and temporarily harsh conditions encountered in natural habitats.